Challenging the Norm: Is Routine Use of Cranial CT in Evaluation of Craniosynostosis Necessary?. Issue 7 (October 2021) - Fahradyan, Artur; Daneshgaran, Giulia; Hoffman, Trevor L.; Wexler, Andrew; Francis, Stacey H.
Abstract : Background: Cranial CT is routinely taught to be the gold standard for diagnosis of craniosynostosis and used by craniofacial teams for suspected nonsyndromic single suture craniosynostosis. Given the risks associated with infant CTs, do these scans provide significantly enhanced diagnostic accuracy compared to the physical exam when performed by an experienced clinical provider? Method: A retrospective chart review was performed for children who underwent corrective surgery for nonsyndromic, single-suture craniosynostosis over an 11 year period by a single craniofacial team. Ages at presentation and surgery, preoperative clinical diagnosis and imaging, co-existing radiographic findings, and correlation with the intraoperative diagnosis were analyzed. Results: A total of 138 patients were included in this study. The mean age was 4.2 months at initial craniofacial evaluation, and 8.0 months at time of surgery. Twenty-seven patients received imaging prior to our clinic. Of those, 21 had plain radiography and 6 had CT scans. Of the remaining 111 patients referred without imaging, craniosynostosis was clinically diagnosed in 102 (92%), whereas 9 (8%) had an unclear clinical diagnosis. Of these 9, 1 (1%) was diagnosed clinically at follow-up exam, and the remaining 8 (7%) were diagnosed using radiography (3 CT scans, 5 plain radiographs). In all patients, the preoperative diagnosis was confirmed during intraoperative assessment. Conclusions: Cranial CT was not needed by experienced craniofacial providers in 93% of nonsyndromic, single-suture craniosynostosis. Imaging obtained before craniofacial clinic referral may have been unnecessary. These findings question the classic teaching that preoperative cranial CT is the gold standard for diagnosis in infants with nonsyndromic, single-suture craniosynostosis. Abstract : Supplemental Digital Content is available in the text